Transition from Oral Folk Culture to Written Form in the Pages of “Sirakarkaj” - Kirakosyan, Hasmik (Bulletin of Yerevan University B: Philology, 2025)
The article discusses the "Sirakarkaj" songbook, published in Calcutta in 1830, within the context of the transition from oral folk to written culture. The compiler of the book brought together Armenian, Persian and Indian folk songs (in Armenian script), in one songbook aimed at an Armenian audience, which also reflects the cultural diversity present in Calcutta at the time. By emphasizing the mediator role of the compiler in transforming oral folk culture into written form, the article raises the question of the extent of the compiler’s intervention in the folk works collected in the songbook. Although the verses in songbook had folk origins, it is a literary material processed by the compiler and presented to the very people who created it, and it is discussed in the context of this circulation. "Sirakarkaj" is an example of secular literature, and in the article, it is analyzed in the context of changes in the printing directions and approaches of the time.